Determining an Effective Marketing Strategy for Promotion on Social Media Platforms: A Case Study of Photography Journey Picture - Tepi Muhammad Romdoni; Enjang Suherman; Laras Ratu Khalida; Kamilah Ahmad (Research in Management of Technology and Business, 2024)
This study aims to determine the most effective promotional strategies for the Journey Picture, a selected Indonesian photography company in order to effectively reach a wide range of customers through online social media platforms. The study employs qualitative research design using a case study, where data collection is carried out through interviews with the owner of Journey Picture Photography. The study is based on internal factor analysis strategy (IFAS) and external factor analysis strategy (EFAS) matrix, SWOT matrix, and Cartesian SWOT analysis diagram. The results show that an IFAS value of 0.05 and EFAS of 0.47, place the SWOT analysis diagram in quadrant 1. This position indicates that the strategy needed by the company is a strength-opportunity (SO) strategy, which utilizes the company’s strengths to capture opportunities. The SO strategy is expected to increase profitability and competitiveness of the company by strengthening existing opportunities and creating new opportunities for the company. It is anticipated that companies can implement an effective growth strategy by overcoming external threats and taking advantage of the many opportunities in the field of photography service. The results of this study provide alternative business development strategies that can be implemented by Journey Picture based on the SWOT analysis.